Unique Phrenic Nerve-Sparing Regional Anesthetic Technique for Pain Management after Shoulder Surgery - Jason K. Panchamia; David A. Olsen; Adam W. Amundson (Case Reports in Anesthesiology)
Background. Ipsilateral phrenic nerve blockade is a common adverse event after an interscalene brachial plexus block, which can result in respiratory deterioration in patients with preexisting pulmonary conditions. Diaphragm-sparing nerve block techniques are continuing to evolve, with the intention of providing satisfactory postoperative analgesia while minimizing hemidiaphragmatic paralysis after shoulder surgery. Case Report. We report the successful application of a combined ultrasound-guided infraclavicular brachial plexus block and suprascapular nerve block in a patient with a complicated pulmonary history undergoing a total shoulder replacement. Conclusion. This case report briefly reviews the important innervations to the shoulder joint and examines the utility of the infraclavicular brachial plexus block for postoperative pain management.